EDUCATION REFORM OF SURABAYA GOVERNMENT THROUGH A PROGRAM OF SANGGAR KEGIATAN BELAJAR - Hidayati, Lutfia Nurul; Holifah, Nur (DIA: Jurnal Administrasi Publik, 2022)
Surabaya has a problem regarding its education system, for instance, the low participation, specifically at the high school level. Many children do not continue their education until their high school years. This problem would hopefully be solved by the Surabaya City government through the Peraturan Walikota Nomor 49 Tahun 2017 on the establishment and organization of a technical implementation unit of non-formal education, Sanggar Kegiatan Belajar (SKB) at the Department of Education of Surabaya. This is a community empowerment program to reduce the dropout rate, particularly for high school students in non-formal educational institutions. This study seeks to observe the conduct of the non-formal education reform by the government of Surabaya. This research is descriptive qualitative by utilizing data collection as its technique, interview, and observation. The interviews were conducted on the determination of informants according to the information required by the researcher. The results showed that education-themed empowerment is to increase students' participation which has not been effective. This is observed through less enthusiasm of dropped out children to participate in the non-formal education in SKB. Supportive actions from the parents are highly expected to encourage their children to participate in their education process to realize the 9-year compulsory education program.